PTU-062 Value of MRI in Predicting Severe outcome in Small Bowel Crohn'S Disease. (4th June 2013) - Rutter, C; Bhatt, S; Sequeiros, I; Burn, P; Thomas, P D
Abstract : Introduction: The optimal approach to managing terminal ileal (TI) Crohn's disease remains to be defined. It is unclear at what stage surgery or biological therapy should be offered and current clinical and biochemical parameters offer poor prediction of disease course. Small bowel MRI scanning (SBMRI) has been correlated with endoscopic and histological disease severity in Crohn's disease and may offer better global assessment of the extent and severity of disease. We aimed to determine which MRI features might predict the need for surgery or biological therapy. Methods: 48 sequential patients with Crohn's disease who underwent SBMRI in a 20 month period to Feb 2011 were identified from a radiological database. 8 patients were excluded due to predominant colonic disease. All remaining 40 patients had confirmed isolated TI disease. Standard management with escalation of therapy via immunomodulors, biological agents and surgery based on clinical follow up was applied. Patients were followed for a minimum of 2 years after the initial MRI. MRI scanning was performed using oral fluid load, IV buscopan, T1/2 axial, coronal and dynamic post contrast sequences. The images were reviewed by a radiologist blinded to outcome of cases and key abnormal features recorded (mesenteric abnormalities, wall thickness > 6 mm, disease extent > 15 cm or proximal dilatation > 25 mm). Patients were then divided into 2 groups, those requiring biological therapy or surgery (severe) and those managed with 5ASA or immunomodulators alone (non severe). Results: The characteristic of the two groups is shown in the table. Means given unless stated. 6/20 patients in the non-severe group (A) had two or more adverse radiological features compared with 12/20 in the severe (B) group (p = 0.06). However, only 3/20 patients had lumen > 25 mm or extent > 15 cm in A compared with 15/20 in B (p < 0.001). Wall thickness and mesenteric involvement were not associated with a severe outcome. Disease extent and proximal luminal diameter were significantly associated with surgery (p = 0.02 and p = 0.0001). 85% of patients who eventually required surgery had either proximal lumen > 25 mm or disease extent > 15 cm. Conclusion: Two or more adverse radiological MRI features are associated with with the need for surgery or biological therapy. Small bowel dilatation > 25 mm proximal to the disease segment and disease extent > 15 cm are particularly associated with the need for surgery. These MRI findings may be helpful in deciding appropriate longer term strategies for managing these patients. Disclosure of Interest: None Declared